FAKTOR RISIKO PENGGUNAAN KONTRASEPSI HORMONAL TERHADAP KEJADIANKANKER PAYUDARA DI RS BHAYANGKARA MAKASSAR - Husnul Hatima; Nurul Fitrahminarsih; Nirwana, Nirwana (Pusat riset dan Inovasi Nasional, 2022)
Women who use hormonal birth control have a 2.990 times greater risk of developing breast cancer than those who do not use hormonal contraceptives. The purpose of this study was to determine the risk factors for the use of hormonal contraception for the incidence of breast cancer. The type of research used is an analytical survey using a case control design. A sample of 88 respondents. The sampling technique was carried out by accidental sampling. The primary data in this study were obtained directly by interviewing respondents who had breast cancer. Secondary data was obtained from the medical records of Bhayangkara Makassar Hospital. Univariate analysis in this study was analyzed using frequency distribution tables and the percentages of each variable studied. Bivariate analysis After conducting univariate analysis, it was followed by bivariate analysis of the two variables that were suspected to be related or correlated, and then the data were analyzed. which shows that the distribution based on the length of use of hormonal contraception in the case group > 2 years is lower (65.9%) than in the control group (72.7%). occurrence of breast cancer. Society should be more cooperative in choosing the right contraception and avoid using contraception which can have a negative impact on health